Contribution of Women from the Sub-Prefecture of Karakoro to the Market Gardening Supply of Korhogo (Côte d’Ivoire) - COULIBALY , Tiécoura Hamed; KONE , Mamadou; BAMBA , Mansé (Revue Internationale du Chercheur, 2025)
Abstract In a context of rapid urban growth and increasing pressure on food supply systems, this study examines the central role of rural women in the Karakoro sub-prefecture in supplying market gardens to the city of Korhogo, the main metropolis in northern Ivory Coast. The results highlight the importance of women in market gardening production and supplying urban markets in Korhogo. In the survey sample, with agricultural areas generally less than 0.5 ha, 35% of women market gardeners in the locality of Karakoro, 20% in Pangarikaha, 20% in Pokaha, 15% in Oléokaha, and 10% in Lavononkaha produce surplus production, which they transport to Korhogo markets. Supply systems rely on direct marketing networks, collection points in villages, and community organization.